The impact of Broadband quality standards on Internet services market structure in Colombia - Julian Hidalgo; Juan D. Oviedo (International Telecommunications Society (ITS), 2014)
This paper develops a structural model which allows estimating the impact of regulatory decisions looking for the setting of download-speed standards on market structure and performance. We characterize a setting under which quality standards improve both service quality and availability. As to quality, we evaluate the impact of quality standards on the performance of local demand from a detailed database of broadband internet subscribers, discriminated by the main attributes of an internet subscription contract as location, supplier, monthly-fee, download- and upload-speed features. From these results, we are able to identify the effect of quality regulation on the behavior of internet providers in a differentiated product market approach. As a consequence, we are able to assert that the response of internet service providers to quality regulation is a more intense product differentiation that contributes to demand expansion and therefore to improve broadband penetration indicators.
Keywords: L51; L96; L86; 330; Regulation; Telecommunication; Information Services; Internet Economics